KONSTRUKSI KALIMAT KESANTUNAN BERBAHASA: KOMUNIKASI MAHASISWA DAN DOSEN STMIK STIKOM INDONESIA - Agus Ari Iswara ,; Ni Nyoman Ayu J. Sastaparamitha, (SPHOTA: Jurnal Linguistik dan Sastra, 2019)
This research aims at analyzing about politeness of STMIK STIKOM Indonesia’s students and lecturers based on their sentence construction in communicating on social media. The data was collected from documentation of their conversation on social media in two semesters of 2017 until 2018. Theory of Pragmatic from Leech and structural theory from Alwi are applied in this research. The research indicates that based on the number of clauses students and lecturers use simple sentence and compound sentence. Based on the syntactic form of the sentence, they use declarative, interrogative, imperative, exclamation, and affirmative sentence. Based on the completeness of the sentence element, they use complete and incomplete sentence. Based on the word sequence pattern, they use regular and inversion word sequence pattern